Can brief telephone interventions reduce caregiver burden and depression in caregivers of people with cognitive impairment? - Long-term results of the German day-care study (RCT) - Donath, Carolin; Luttenberger, Katharina; Grässel, Elmar; Scheel, Jennifer Felicia; Pendergrass, Anna; Behrndt, Elisa-Marie (BMC Geriatrics, 2019)
Background: Day-care and telephone counseling have been discussed as effective support measures for caregivers of people with cognitive impairment. Methods: In a two-arm cluster-randomized trial involving multicomponent therapy for cognitively impaired persons in day-care centers and telephone counseling for their caregivers versus treatment as usual (TAU), we investigated long-term effects on caregivers' burden and depressiveness. Person-caregiver dyads involving home-dwelling persons with MCI, mild dementia, or moderate dementia were eligible. Day-care centers were randomized into an intervention group (IG) or a control group (CG). Outcome assessors were blinded. Out of 359 caregivers who had completed a 6-month intervention phase (nIG = 205, nCG = 154), a total of 304 of them were available at the 12-month follow-up (nIG = 173, nCG = 131). Instruments for assessing were the Burden Scale for Family Caregivers - short version (BSFC-s) (caregiver burden) and the Well-Being Index Score (WHO-5) (depressiveness). Mixed ANOVAs were used for the main analyses; descriptive statistics and subgroup analyses were additionally performed; secondary analyses involved multiple linear regressions for the main outcomes that were significant in the unadjusted main analysis. Results: At follow-up, crude mean differences showed a nonsignificant advantage for the IG in caregiver burden [IG: -.20 (SD = 5.39) vs. CG:.76 (SD = 5.49), p =.126, d =.177] and depressiveness (reverse scored) [IG: -.05 (SD = 5.17) vs. CG: -.98 (SD = 5.65), p =.136, d =.173]. For caregiver burden, a mixed ANOVA resulted in significant main effects of group (F (1, 302) = 4.40; p =.037) and time (F (1.88, 568.96) = 3.56; p =.032) but not a significant interaction. The largest effects were found for the "mild dementia" subgroup (d =.443 for caregiver burden and d =.520 for depressiveness). Discussion: Positive long-term effects of a combined intervention involving telephone counseling for caregivers and multicomponent activation for patients were observed especially for mild dementia. However, the treatment effects washed out after the intervention ended. Trial registration: ISRCTN16412551 (date: 30 July 2014, retrospectively).
CRIS-Team Scopus Importer:2019-08-06
Keywords: Day-care; Dementia; MCI; Informal caregivers; Telephone intervention